Culture in English Language Teaching: A curricular evaluation of English textbooks for foreign language learners - Banaruee, Hassan; Farsani, Danyal; Khatin-Zadeh, Omid (Frontiers in Education, 2023)
A critical assessment of the current systematical planning and an in-depth review of the teaching materials efficiently improve fine educational materials to the benefit of developed learning and teaching contexts. In some countries, such as Iran, that belong to the expanding circle, local book writers provide English teaching materials that may ignore sociopragmatic language components, particularly culture. There is a blind spot and massive gap in the related literature regarding the inclusion and organization of cultural knowledge in these textbooks. This study investigated culture in Iranian schools by conducting a nationwide survey to fill the gap. The investigation was based on the components of the curriculum administered and used in Iran, namely Vision Series. The evaluation was aimed at two prospects; firstly, to interpret whether the English textbooks taught at high schools in Iran have standardized principles and elements regarding Communication and Culture. Secondly, to investigate the extent to which cultural knowledge and technology as the curricular components are implemented in the Vision Series. In this respect, the 5 Cs checklist developed by the American Council on the Teaching of Foreign Languages was employed. The evaluation done by 120 English language teachers reveals that the textbook Vision 3 is more preferable and desirable than Vision 1 and 2, yet not significantly. The evaluation based on the seven curricular components indicates that Vision textbooks have standards at a low level and are not designed and developed to enhance language learners’ cultural competence in the target language. This study highlights the role of enhancing language learners’ cultural awareness in the expanding circle of World Englishes.